Implementation of Supervision of Development Planning Using and Impact of Information Technology at the Office of Bappeda, Southeast Minahasa District - La Abu,; Masengi, Evi E.; Mamonto, Fitri H. (International Journal of Information Technology and Education, 2023)
This research discusses the supervision, and planning, development of the Development Planning Agency (BAPPEDA) Office Southeast Minahasa District. This study aims first, to know and analyze as well as illustrate planning development in the district of Southeast Minahasa. Second, that is a known and analyzed factor determinant of planning development in the Southeast Minahasa district. The type of study is qualitative. The informant main is the Head of the District Development Planning Agency (Bappeda) Southeast Minahasa. Besides That, informant other that is functional nor Apparatus State Civil Service (ASN) in scope Bappeda Regency Southeast Minahasa, head village, Representative Body Village (BPD), figure community, youth and women representatives in the District Ratahan and East Ratahan Southeast Minahasa Districts. Data was obtained through interviews, observation, and documentation. Next, this research analyzed with a technique that the validity of data is based on the belief that with criteria This level existing beliefs already true, That is, stage This part from the validation process. Results of the research show that BAPPEDA supervision in planned programs is Still not enough stable. BAPPEDA still faces challenges in the supervision of planned programs related to development. The challenge in system BAPPEDA's planning lies yet effectiveness supervision, esp related to the extent of the planned programs following the plan beginning. Some of the programs it turns out Not yet following plans that have been set initially. One suggestion is an implementation of e-supervision in planning to get it held in real time.